Rekonstruksi Sejarah Dan Transformasi Cagar Budaya Istana Almukarramah Kesultanan Sintang - Muhammad Aqif Alghifari; Andang Firmansyah; Mohammad Rikaz Prabowo (STKIP Singkawang, 2006)
The Almukarramah Palace of the Sintang Sultanate is a Cultural Heritage site that must be preserved. Periodic research is one of the efforts to support its preservation. This study aims to reconstruct the historical narrative based on newly discovered data and to describe the current condition of the palace building. The local community is expected to be encouraged to utilize the palace, particularly institutions engaged in history, education, and tourism. This research uses a qualitative method with historical and architectural approaches. The historical approach is used to reconstruct historical information, including heuristics, verification, interpretation, and historiography. The architectural approach is applied to describe the physical form of the object. Primary and secondary data were collected through observation, interviews, and literature studies. The results show that the palace has stood in the Kampung Raja area since Sintang was a Hindu kingdom. However, the structure currently standing was built when Sintang became an Islamic kingdom, specifically during the reign of Panembahan Raden Abdul Bahri Danu Perdana Al-Mukarram Kesuma Negara IV. The construction of the Sintang Sultanate Palace was full of dynamics, ranging from disputes between the Panembahan and the Dutch colonial government to the sinking of a ship carrying construction materials. Observations also revealed many historical objects around the palace. One of the new contributions of this research is the documentation of the changes in the building’s function and its renovation history after Sintang's integration into Indonesia.